Challenging old microbiological treasures for natural compound biosynthesis capacity - Nouioui, Imen; Zimmermann, Alina; Hennrich, Oliver; Xia, Shuning; Rössler, Oona; Makitrynskyy, Roman; Pablo Gomez-Escribano, Juan; Pötter, Gabriele; Jando, Marlen; Döppner, Meike; Wolf, Jacqueline; Neumann-Schaal, Meina; et al. (Frontiers in Bioengineering and Biotechnology, 2024)
Strain collections are a treasure chest for numerous valuable and taxonomically validated bioresources. The Leibniz Institute DSMZ is one of the largest and most diverse microbial strain collections worldwide with a long tradition of actinomycetes research. Actinomycetes, especially the genus Streptomyces, are renowned as prolific producers of antibiotics and many other bioactive natural products. In light of this, five Streptomyces strains, DSM 40971T, DSM 40484T, DSM 40713T, DSM 40976T, and DSM 40907T, which had been deposited long time ago without comprehensive characterization, were the subject of polyphasic taxonomic studies and genome mining for natural compounds based on in vitro and in silico analyses. Phenotypic, genetic and phylogenomic studies distinguished the strains from their closely related neighbors. The digital DNA-DNA hybridization and average nucleotide identity values between the five strains and their close, validly named species were below the threshold of 70% and 95 - 96%, respectively, determined for prokaryotic species demarcation. Therefore, the five strains merit to be considered as novel Streptomyces species, for which the name Streptomyces kutzneri sp. nov. Streptomyces stackebrandtii sp. nov., Streptomyces zähneri sp. nov., Streptomyces winkii sp. nov. and Streptomyces kroppenstedtii sp. nov. are proposed. Bioinformatic analysis of the genome sequences of the five strains revealed their genetic potential for the production of secondary metabolites, which helped for the identification of the natural compounds cinerubin from strain DSM 40484T and the phosphonate antibiotic phosphonoalamide from strain DSM 40907T, as well as highlighted strain DSM 40976T as candidate for regulator-guided gene cluster activation due to the abundance of numerous ‘Streptomyces antibiotic regulatory protein’ (SARP) genes.